You are on page 1of 2

1

()()

Tbp

bpd =

bpd

(

bpd

=RTbp ln x

bpd

= RTbp x

)
V

= S
T P

RTbp2
Tbp =
H vap

= S
Tbp ,

= S
Tbp

Tbp

(1)

x + x = 1,
x << 1
(
)
(2)

S S =

bpd

RTbp ln x

bpd

= RTbp x

Tbp

S vap

S vap =
H va p / T

()()

AS (
AS
( )), k / k = K (
k , k
()(
)()) P

(1- )

Langmuir

(1) Langmuir
(2) ()(a)(b) P

(a) P (KP<<)(b) P KP>>1


( g ) + S

( g ) , S

voff

= k 1 [
S]

von = k1 [ ( g ) ][ S ]

voff

= von

Clausius-Clapayron

H vap

d G = d G

Maxwell

d G = V dP SdT

V dP S dT = V dP S dT

d (ln P )
H vap
=
d (1 / T )
R

Clausius-Clapayron

H vap 1

ln P =
+ const .

R
T

ln P

1
T

H vap

(-)()

C x
( A,B (
)
)
1 C x
2
A + B C

C A0 ,

t = 0

C B0

()>>()( C >> C ) 1
S E (- ES)
S0

E0

k1

k2
P E + S ES , ES P
k 1

KM

v=

k 2C E 0
1 + K M CS 0

KM =

C C
k1 + k2
= E S
k1
C ES

()

( v )